The Meaning of Brand Awareness, Brand Experience, and Brand Engagement in Building Consumer Loyalty - Ramadhani, Citra Nia; Ikaningtyas, Maharani (Borong Newinera Publisher, 2025)
This study aims to analyze consumer loyalty towards Kopi Tuku through three main variables, namely brand awareness, brand experience, and brand engagement. This research uses a descriptive method with a qualitative approach. The research subjects consist of six consumers who have consistently purchased Kopi Tuku for the past two years. Data collection techniques in this study were carried out through observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman model, which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that Kopi Tuku's brand awareness is not only formed from visual recognition such as logos or packaging but has reached the highest level, namely top of mind. Brand experience is felt through sensory, affective, intellectual, and behavioral dimensions, making Kopi Tuku not only a beverage provider but also part of the consumers’ routines and identities. Meanwhile, brand engagement is reflected in strong emotional involvement, repeated purchasing habits, participation in trying new products, and ownership of merchandise. This study emphasizes that consumer loyalty towards Kopi Tuku is not solely built on product quality or price but through the synergy between brand awareness, brand experience, and brand engagement, which creates a personal and emotional connection between consumers and the brand.